(untitled) (Journal of International Studies, 2020)
The British colonial rule in Bengal had a very ominous impact on the people of the region as a whole. The introduction of a new land tenure system, known as the Permanent Settlement, and the creation of an all-powerful zamindar class particularly affected the interests of the peasants of Bengal. Under the new system, the government demand on the zamindars was fixed in perpetuity, but there was no legal restriction on the zamindars to enhance their share from the peasants. The peasants, consequently, became vulnerable to irregular rent increases and oppressions by the zamindars. The Faraizi movement, organized initially in the nineteenth century to reform the Muslim society, soon assumed the character of agrarian movement. In order to protect the poor peasants, the Faraizis soon became radical and challenged the zamindars. As majority of the peasants of the region, where this movement was launched, were Muslims and their zamindars mostly Hindus, the Faraizis used Islamic symbols to mobilize the Muslim masses. Thus, religion and economy intertwined in shaping such a protest movement in pre-industrial Bengal.